OPTIMIZATION OF PRODUCT INCORPORATING INDIAN BLACKBERRY (SYZYGIUM CUMINI) SEED FLOUR: A DIABETIC STUDY - E, Lakshmi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this study was to optimize recipes incorporating Indian blackberry (Syzygium cumini) seed flour (SCSF) in biscuits for its organoleptic feel and assess its impact on the anthropometric status of Type 2 diabetes mellitus. Method: The study was designed to include 20 Type 2 and 20 normoglycemic controls. Biscuits were prepared using four blends (10 g, 15 g, 20 g, and 25 g) of SCSF with a control. The diabetic subjects were supplemented with Indian blackberry SCSF (20 g) biscuits. Nutritional status was assessed such as body mass index (BMI) and waist-hip ratio (WHR). Results were analyzed statistically by two-way ANOVA and paired t-test. Results: Statistically, there was a significant difference (p<0.001) in flavor and taste perception between diabetics and normoglycemic. The mean fasting and postprandial glucose level decreased much (p<0.001). There was a significant (p<0.001) decrease in the BMI and WHR